Brain mechanism of Chinese character processing in rapid stream stimulation. (August 2022) - Chen, Juan; Sun, Dan; Wang, Peng; Lv, Yating; Zhang, Ye
Abstract: In visual masking, the visibility of a fleetingly presented visual target is disrupted by the presentation of an additional image, the mask, shortly before or after the target. Rapid stream stimulation (RSS) is a masking paradigm that is frequently used in character processing. Although neuroimaging studies have examined lexicality in terms of RSS, the mechanism underlying character masking has not been investigated. To resolve this issue, we investigated the neural basis of masking effects in lexicality using a two-way factorial design in a 3T-fMRI with masking (mask condition: masked versus unmasked) and target stimulus (character likeness: real-, pseudo-, non-characters) as factors. We found that brain activity in the left middle occipital gyrus (MOG) and lingual gyrus was strongest in the unmasked condition in RSS. Analysis of psychophysiological interactions revealed diverse patterns of functional connectivity in the two conditions, with stronger functional connectivity of the left MOG to the left fusiform gyrus and the right posterior cingulate cortex, suggesting the involvement of lexical processing of familiar characters. Together, these findings of activation and connectivity patterns indicated that masking in RSS reduced the visibility of characters by suppressing activity in the occipital cortex and reduced connectivity in both orthographical and attention networks. Highlights: Masks in the rapid stream stimulation degraded the visibility of Chinese characters in language-related regions. Masks in the rapid stream stimulation reduced the top-down influence of attention. The more word-likeness stimuli contain more meaningful information were less disturbed by masks.